The vascular endothelium - Moncada1, Salvador (2014)
Over the last 40 years, research on the vascular endothelium has provided important clues for the understanding of vascular disease. This new knowledge is finding its way into clinical medicine. In this review we deal with some areas where significant advances in the prevention and treatment of cardiovascular research has been achieved and with some of the remaining questions.